New paths in Austrian Macroeconomics - Barnet II, William Barnet II; Block, Walter E. Block (REVISTA PROCESOS DE MERCADO, 2013)
This paper makes four points. First, interest rates are not prices; rather they are metrics. Second, there are no markets for «loanable funds» in reality, so attempts to use «the» market for loanable funds either to explain saving-induced growth (or growth induced in other ways) are misleading. Rather, the appropriate concept is markets for financial assets. Third, the primary and most important source of growth is not households’ low or reduced time preferences, but entrepreneurs high or increased profit expectations. Fourth, financial institutions may respond, in part, to a rise in the monetary base by accepting a higher default risk of their assets; i.e., by making riskier loans and buying riskier (financial) assets, in order to maintain nominal interest rates and net interest margins. Key words: Risk, Loanable funds, Financial assets, Austrian business cycle theory. JEL Classification: E32. Resumen: Este artículo desarrolla una versión modificada de la teoría austriaca del ciclo económico en la que el papel protagonista lo juegan las expectativas de beneficio de los empresarios (más que la reducción de la preferencia temporal de los agentes económicos) y la asunción de proyectos empresariales más arriesgado, como principal detonante de las malas inversiones. Palabras clave: Riesgo, Fondos prestables, Activos financieros, Teoría austriaca del ciclo económico. Clasificación JEL: E32.